Implementation of sugar-sweetened beverages tax and its perception among public health stakeholders. A study from Poland - Brukało, Katarzyna; Kaczmarek, Krzysztof; Kowalski, Oskar; Romaniuk, Piotr (Frontiers in Nutrition, 2022)
Background. One of tools to tackle growing problem of overweight and obesity are the taxation mechanisms applied to sugar-sweetened beverages, which are expected to influence the common eating behaviours, but also they have impact on the market and public finances. The solution is therefore highly entangled in the complex of social and intersectoral interests generating a number of opportunities and threats affecting its feasibility. Aims. The study aims to depict the views of Polish stakeholders on the implementation of the sugar tax in Poland, particularly the perception of success determinants, barriers, as well as views on the features of the implemented solutions and possible alternatives. Methods. We used semi-structured interviews with 18 individuals representing key public health stakeholders in Poland. The interview consisted of four parts, where first concentrated on the advantages and disadvantages of the SSB tax, the second part explored stakeholder involvement and stances, third concerned the feasibility of the project, and in the fourth part respondents were asked for suggestions for decision-makers regarding the content of the project and its implementation process. To reconstruct position of 4 main political parties we applied desk research. We used MAXQDA v2020 to analyse the collected data. Results. Stakeholders tend to expressed conflicting views on the effectiveness, relevance and socio-economic impact of the SSB tax. All of them agreed that the tax may appear severe for the poorest groups, children and adolescents, while disagreeing about the economic impact of the levy. The allocation of additional tax revenues was raising doubts, with stakeholders believing that the fiscal aim is the basic reason for implementing the tax, while these resources should be primarily dedicated to health promotion intervention and prevention of diet-related diseases. On the other hand, the political debate on the tax was highly superficial with strong populism arising of the presented positions. Conclusions. There is a need to conduct a thorough public debate and improvements in terms of public communication to increase social awareness, sealing and refining the implemented solutions. Close cooperation with market players and non-governmental organizations is highly recommended.